1993
DOI: 10.5271/sjweh.1470
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial factors at work and musculoskeletal disease.

Abstract: BONGERS PM, de WINTER CR, KOMPIER MAJ, HILDEBRANDT VH. Psychosocial factors at work and musculoskeletal disease. Scand J Work Environ Health 1993; 19:297-312. The objective of this review is to establish whether the epidemiologic literature presents evidence of an association between psychosocial work factors and musculoskeletal disease. In a hypothetical model it is suggested that individual characteristics and stress symptoms can modify this relationship. The reviewed studies do not present conclusive eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

46
664
8
35

Year Published

1996
1996
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 954 publications
(766 citation statements)
references
References 32 publications
46
664
8
35
Order By: Relevance
“…An estimation of physical demands by self-reports has been criticised as being inaccurate, especially for the more complex load-bearing activities carried out by employees [67]. Otherwise, it has been shown that workload and occupational physical activity can be reliably assessed by questionnaires and that questionnaires can classify groups with heterogeneous occupational tasks [68][69][70][71][72][73][74][75][76].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An estimation of physical demands by self-reports has been criticised as being inaccurate, especially for the more complex load-bearing activities carried out by employees [67]. Otherwise, it has been shown that workload and occupational physical activity can be reliably assessed by questionnaires and that questionnaires can classify groups with heterogeneous occupational tasks [68][69][70][71][72][73][74][75][76].…”
Section: Discussionmentioning
confidence: 99%
“…It is generally agreed that the aetiology of back pain is multifactorial [74] and that physical load only partially explains the prevalence of back pain [75]. There is robust evidence that psychological factors are related to future episodes of back pain and its related disability [76][77][78]. Three studies [29,31,53] demonstrated in a multidisciplinary approach that not mechanical factors alone but a combination of sociodemographic, work-related and psychosocial factors was important in predicting new onsets of LBP.…”
Section: Discussionmentioning
confidence: 99%
“…One such factor may involve work-related stress, which has been connected to the development of musculoskeletal (Bongers et al 1993;Östergren et al 2005), psychiatric (Stansfeld and Candy 2006) and cardiovascular (Belkic et al 2004;KivimĂ€ki et al 2006) disease. The three also comprise the most common diagnostic groups that account for retirement on grounds of ill health (Alexanderson and Norlund 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological research, especially from the Whitehall studies, has been generally supportive of the hypothesis suggesting a relationship between the psychosocial work environment, work related stress and health status. Specifically, high strain jobs (high demand combined with low control) are associated with adverse health outcomes, including increased risk of heart disease, Karasek et al, 1981;Kuper & Marmot, 2003) musculoskeletal pain, (Bongers et al, 1993) poor mental health, (Stansfeld S, 1999) and sickness absence. (North et al, 1996) High strain jobs are concentrated amongst lower socio-economic groups and thus, the psychosocial work environment is considered an important influence on health inequalities amongst the working population.…”
Section: Introductionmentioning
confidence: 99%